Karakteristik Kimia Rumput Laut Hijau (Caulerpa microphysa dan Codium sp) dari Perairan Kepulauan Riau: tes - Aidil Fadli Ilhamdy; Jumsurizal Jumsurizal; Azwin Azwin; Satrio Manggala Bahari; Ginanjar Pratama (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Green seaweed is one of the leading marine products from the Riau Islands Province. Types of green seaweed such as Caulerpa microphysa and Codium sp. have potential as functional and pharmaceutical food, but their utilization is not optimal in the Riau Islands region. This study aims to examine the proximate characteristics of seaweed types C. microphysa and Codium sp. The method used in this research is seaweed sampling in the coastal of Natuna and Tanjungpinang, which are the Riau Islands region with abundant green seaweed commodities. The next method is the proximate analysis of dried seaweed, which includes analysis of water content, ash, protein, fat, and carbohydrates and calculating the total energy and energy from fat. The results showed that the proximate content of C. microphysa and Codium sp. respectively for moisture content was 19.88 ± 0.14 and 11.29 ± 0.08%, the ash content was 30.74 ± 0.27 and 55.51 ± 0.41%, protein is 8.97 ± 0.08 and 6.84 ± 0.12%, total fat is 1.20 ± 0.01 and 1.09 ± 0.01%, carbohydrates are 39.22 ± 0.32 and 25.28 ± 0.37%, energy from fat is 10.76 ± 0.06 and 9.77 ± 0.06 Kcal / 100g, total energy is 203.49 ± 1.68 and 138.23 ± 2.02 Kcal / 100g. These results indicate that the type of seaweed C. microphysa is better than Codium sp. in chemical composition and total energy.